Implementation of a Defecation Posture Modification Device: Impact on Bowel Movement Patterns in Healthy Subjects. Issue 3 (March 2019) - Modi, Rohan M.; Hinton, Alice; Pinkhas, Daniel; Groce, Royce; Meyer, Marty M.; Balasubramanian, Gokulakrishnan; Levine, Edward; Stanich, Peter P.
Abstract : Goals: The goal of this study was to evaluate the influence of defecation postural modification devices (DPMDs) on normal bowel patterns. Background: The introduction of DPMDs has brought increased awareness to bowel habits in western populations. Materials and Methods: A prospective crossover study of volunteers was performed that included real-time collection of data regarding bowel movements (BMs) for 4 weeks (first 2 wk without DPMD and subsequent 2 wk with DPMD). Primary outcomes of interest included BM duration, straining, and bowel emptiness with and without DPMD use. Results: In total, 52 participants (mean age, 29 y and 40.1% female) were recruited for this study. At baseline 15 subjects (28.8%) reported incomplete emptying, 23 subjects (44.2%) had increased straining, and 29 subjects (55.8%) noticed blood on their toilet paper in the past year. A total of 1119 BMs were recorded (735 without DPMD and 384 with DPMD). Utilizing the DPMD resulted in increased bowel emptiness (odds ratio, 3.64; 95% confidence interval (CI), 2.78-4.77) and reduced straining patterns (odds ratio, 0.23; 95% CI, 0.18-0.30). Moreover, without the DPMD, participants had an increase in BM duration (fold increase, 1.25; 95% CI, 1.17-1.33). Conclusions: DPMDs positively influenced BM duration, straining patterns, and complete evacuation of bowels in this study.